Evaluating revenue administration and land records: their strengthening and updating in Mizoram / by Prem Singh, Saroj Arora and L. C. Singhi - Singh, Prem (Mussoorie, 2012)
This book about study Evaluating Revenue Administration and Land Records. Their Strengthening and Updating in Mizoram' has been conducted on behest of the Ministry of Rural Development, Department of Land Resources, Government of India.
Keywords: Revenue administration-Mizoram